(untitled) (Innovation in Woodworking Industry and Engineering design, 2026)
Working in a CNC machines is one of the most popular woodworking processes. Often is more suitable to use Subtractive Rapid Prototyping (SRP) machines than classic CNC machines. In the current study the surface roughness checked for two different wood kinds, wenge and maple. For each kind of wood six specimens milling in a 3-axis SRP machine and then the surface roughness average (Ra) defined. During milling process two different tools used. For roughing phase, a square end mill and then a ball end mill for finishing. For roughness check a portable linear roughness tester instrument used to define the Roughness Average (Ra) for each specimen. During the milling process the spindle speed and fed rate varies. The spindle speed starts from 1.100 mm/min until to 2.400mm/min and feed rates starts from 9.00 rpm to 15.000 rpm. According to the results the changes in machining parameters have significant effect to surface quality. Wenge is harder than maple wood and that play an important role to surface roughness. As cutting parameters improved roughness average (Ra) is less.